Acetic acid mediated regioselective synthesis of 2, 4, 5-trisubstituted thiazoles by a domino multicomponent reaction. (20th May 2019) - Saroha, Mohit; Khurana, Jitender M.
Abstract : Acetic acid mediated regioselective synthesis of novel 2, 4, 5-trisubstituted thiazole derivatives has been reported by a domino reaction of thiosemicarbazide and aldehydes/ketones/isatin, to generate thiosemicarbazones ( in situ ) followed by addition of arylglyoxal and active methylene/activated C–H acids/pyrazole/indole in ethanol at 80 °C. Abstract : Acetic acid mediated regioselective synthesis of novel 2, 4, 5-trisubstituted thiazole derivatives has been reported by a domino reaction of thiosemicarbazide and aldehydes/ketones/isatin, to generate thiosemicarbazones ( in situ ) followed by addition of arylglyoxal and active methylene/activated C–H acids/pyrazole/indole in ethanol at 80 °C. The products are obtained in high yields by a simple work up. Metal free, short reaction time and high yields are some merits of this methodology.